2019
DOI: 10.3390/met9040401
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and Evaluation of Theoretical Forming Limit Diagram of Al 6061-T6 in Electrohydraulic Forming Process

Abstract: The current study examines the forming limit diagram (FLD) of Al 6061-T6 during the electrohydraulic forming process based on the Marciniak–Kuczynski theory (M-K theory). To describe the work-hardening properties of the material, Hollomon’s equation—that includes strain and strain rate hardening parameters—was used. A quasi-static tensile test was performed to obtain the strain-hardening factor and the split-Hopkinson pressure bar (SHPB) test was carried out to acquire the strain rate hardening parameter. To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The results showed that the M-K model with J-C model is more suitable to calculate the biaxial strain limit of AA5A06 at high strain rates when compared with the Swift model. Woo et al [13] studied the electrohydraulic FLC of 6061-T6 aluminum alloy based on M-K theory and Hollomon model including strain hardening and strain rate hardening parameters. The predicted electro-hydraulic FLC is in good agreement with the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the M-K model with J-C model is more suitable to calculate the biaxial strain limit of AA5A06 at high strain rates when compared with the Swift model. Woo et al [13] studied the electrohydraulic FLC of 6061-T6 aluminum alloy based on M-K theory and Hollomon model including strain hardening and strain rate hardening parameters. The predicted electro-hydraulic FLC is in good agreement with the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…This process enables aluminum alloy sheets to be accelerated to a speed of ≥100 m/s and subjected to a high strain rate of 100 s −1 . Corresponding numerical simulations have also been conducted [32,33]. Electromagnetic seam welding has also been studied, in which aluminum sheets are joined using powerful electromagnetic pulse technology [34,35] and then joined to magnesium alloys heated to 200-300 • C [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…The ductile fracture behavior of the anisotropic 7050-T7451 aluminum alloy plate was investigated, and a novel damage model was proposed to predict the fracture behavior of anisotropic materials [32]. In addition, the theoretical forming limit diagram (FLD) of Al 6061-T6 was acquired and evaluated in an electrohydraulic forming process [33]. The physical model and numerical simulation of a deep drawing process for a box-shaped product were developed, and the best combination of yield locus and hardening law was determined [34].…”
Section: Introductionmentioning
confidence: 99%